2013
DOI: 10.5114/wiitm.2011.32809
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of stereoscopic liver surface reconstruction.

Abstract: IntroductionTracking abdominal motion of organs is an important factor in image-guided navigation systems. The paper presents the evaluation methodology of a practical approach to measure liver motion, both respiratory and laparoscopic, with a tool guided in the operating room. AimEvaluation of the methodology of a practical approach to measure liver motion, both respiratory and laparoscopic, with a tool guided in the operating room. Material and methodsThe presented evaluation method is based on standard oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The common problem of fiducial markers attachment is its physically invasive character, always causing some level of danger during the treatment. In the past years those two limitations have been studied and other propositions have been formulated, mostly for the more demanding soft tissue surgery [ 18 , 19 ]. The noninvasiveness requirement is being overcome by the surface matching techniques replacing marker matching approaches [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The common problem of fiducial markers attachment is its physically invasive character, always causing some level of danger during the treatment. In the past years those two limitations have been studied and other propositions have been formulated, mostly for the more demanding soft tissue surgery [ 18 , 19 ]. The noninvasiveness requirement is being overcome by the surface matching techniques replacing marker matching approaches [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of IGI systems is presenting a model of the operation field including tumors and positions of surgical tools on an extra medical monitor, which shortens the intervention and improve safety in general [ 7 ] and for liver ablation [ 8 ]. Tracking points of the liver is a complex process, whose accuracy is also influenced by parameters of the stereo camera, which was set up by two laparoscopic monocular cameras and the calibration procedure [ 9 ]. Previous work has shown that mobility of the individual points of the liver reaches millimeters due to respiratory motion or even centimeters under pressure of laparoscopic tools [ 10 ].…”
Section: Introductionmentioning
confidence: 99%